A Stress-Induced Martensitic Transformation in Aged Ti(49)Ni(51) Alloy after High-Velocity Impact - Zhu, Yingying (Materials (Basel), 2016)
The effects of a high-velocity impact on the microstructure, phase transformation and mechanical property of aged Ti(49)Ni(51) alloy are investigated. The transformation behavior and microstructure along the impact direction after impact emerge with regionalization characteristics, including a deformed region near the crater (0–4 mm) and an un-deformed region of the distal crater (5–6 mm). Stress-induced martensite is the main deformation mechanism in the deforming region of aged Ti(49)Ni(51) alloy under high-velocity impact.